Improvement of cyclodextrin glycosyltransferase biosynthesis by recombinant Lactococcus lactis NZ:NSP:CGT - Amiri, Azin (2014)
Cyclodextrin glycosyltransferase (CGTase) is a distinctive enzyme that has the capability of producing cyclodextrin (CD) from starch. The CD as the product of CGTase has numerous applications in various industries such as foods, cosmetics and toiletries, textiles and agrochemistry. Therefore, CGTase is considered as an industrially important enzyme and its production improvement is very crucial. So,essential efforts to increase its activity are desirable. CGTase production has never been investigated in Generally Regarded as Safe (GRAS) organism, Lactococcus lactis despite its advantages. The CGTase biosynthesis by recombinant Lactococcuslac tis NZ:NSP:CGT using different carbon sources ((corn starch), potato (dextrin from starch), tapioca starch and several soluble potato starches) and nitrogen sources (yeast extract, meat extract, peptone from meat, peptone from soymeal and peptone from casein) was carried out in batch cultivation using 250 mL shake-flask. Statistical optimization was performed using artificial neural network technique in order to optimize the culture condition (temperature) and medium compositions (carbon and nitrogen sources concentrations) to achieve maximum CGTase production. The experimental data from the aforementioned fermentation experiments were analyzed in order to obtain the kinetic parameter values and establish the basis of a kinetic model. The optimum parameters obtained were used to run batch fermentation in a 2L stirred tank bioreactor. The best carbon source leading to maximum CGTase biosynthesis was determined as Nacalai Tesque GR soluble potato starch. The maximum CGTase activity and productivity obtained by this carbon source were 7.99 U/mL and 1 U/mL.h, respectively. Yeast extract (Merck) was selected as the best nitrogen source due to its highest CGTase activity (9.88 U/mL) and productivity (0.99 U/mL.h) obtained. In screening stage of CGTase fermentation, carbon source concentration, nitrogen source concentration and temperature were recognized as three significant fermentation parameters. The optimum values for these parameters were determined through statistical optimization as 20°C for temperature and 3.82 and 5.67% (w/v) of soluble starch and yeast extract concentrations, respectively. The maximum CGTase activity obtained using the optimum values was 22.09 U/mL, which was closed to the predicted value (24.17 U/mL). The models used in this study were based on unstructured model equations including logistic and Luedeking-Piret, which were suitable to explain the growth, substrate consumption and CGTase production by L. lactis NZ:NSP:CGT in batch cultivation. According to the results, CGTase production is a growth-associated process. Production of CGTase in 2L stirred tank bioreactor (15.36 U/mL) was lower than shake-flask, which shows the essential optimization studies in bioreactor scale.